Clinical characteristics and natural history of pre-adolescent non-syndromic hypertrophic cardiomyopathy. (14th October 2021) - Cleary, A; Norrish, G; Field, E; Cervi, E; Kaski, J P; ,
Abstract: Background: The clinical presentation and natural history of pre-adolescent sarcomeric hypertrophic cardiomyopathy (HCM) has not been systematically characterised. The aim of this study was to describe the clinical characteristics and outcomes of a large, international, multicentre cohort of children diagnosed with non-syndromic HCM below the age of 12. Methods: Data from the International Paediatric Hypertrophic Cardiomyopathy Consortium on 639 children meeting diagnostic criteria for HCM below 12 years of age (pre-adolescent) were collected and compared with 568 diagnosed aged 12–16 years. Patients with syndromic and metabolic HCM were excluded. Results: Of 639 (male n=417, 65.3%) children with pre-adolescent HCM, 339 (53.1%) had a family history of HCM and 57 (8.9%) a family history of sudden cardiac death (SCD). At the time of baseline assessment; 132 (20.7%) had heart failure symptoms and 39 (6.1%) reported unexplained syncope. Median maximal left ventricular wall thickness on echocardiogram was 13.6mm (IQR 10–19) with a corresponding median z-score of 8.7 (5.3–14.4). 145 (22.7%) had left ventricular outflow tract obstruction (LVOTO) (maximal LVOT gradient≥30mmHg) and 35 (5.5%) had severe LVOTO (gradient≥90mmHg). Over a median follow up 5.6 years (IQR 2.3–10), 10.5% underwent a myectomy and 23.2% implantable cardiac defibrillator (ICD) implantation for primary (81.8%) or secondary (14.2%) prevention. 42 (6.7%) patients died [SCD 4.9%, heart failure death 0.8%, other 1%] and 21 (3.3%) underwent cardiac transplantation. 69 (10.8%) patients had an arrhythmic event (SCD n=31, resuscitated cardiac arrest n=17, appropriate ICD therapy n=14, sustained VT with haemodynamic compromise n=7). Compared to those presenting after 12 years, those under 12 were less likely to have a family history of SCD (8.9% vs 13%, p:0.047) or report unexplained syncope (6.1% vs 12.3%, p<0.00). The degree of hypertrophy did not differ but a higher proportion of pre-adolescent patients had LVOTO (22.7% vs 14.4%, p<0.00). A higher proportion of pre-adolescent underwent a myectomy (10.5% vs 7.2%, p:0.045) but a lower proportion received a primary prevention ICD (18.9% vs 30.1%, p:0.041). The overall proportion of patients reaching the mortality or arrhythmic end-points did not differ, but SCD and resuscitated cardiac arrest events were more frequent in pre-adolescent patients (4.9% vs 3.9% and 2.7 vs 1.6% respectively). Conclusion: Pre-adolescent HCM is associated with a high symptom burden and variable cardiac phenotype, comparable to those presenting later in childhood. Despite baseline similarities and equal overall survival, younger patients were less likely to receive a primary prevention ICD despite being more likely to experience a SCD or resuscitated cardiac arrest. This study suggests that younger patients should not be considered a distinct entity for risk stratification and that similar management strategies to older HCM patients should be employed. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): BHF (British Heart Foudnation) MRC (Medical Research Council)